Kesiapan Kerja Generasi Milenial di DKI Jakarta Raya: Pengaruh Kecerdasan Emosional dan Keterampilan Digital - Jihan Sabilah; Silvania Nurfandi Riyanti; Nopriadi Saputra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to determine the level and effect of emotional intelligence and digital skills on the work readiness of the millennial generation in DKI Jakarta. Research Methodology: This study was based on quantitative approaches using the computation of regression. It used primary data through the questionnaire distribution with 401 respondents of the millennial generation in DKI Jakarta. Results: The results of the study indicate that emotional intelligence and digital skills influence work readiness. Limitations: This research only assessed emotional intelligence, digital skills, and work readiness variables, and only the millennial generation in DKI Jakarta. Contribution: This study shows the level of emotional intelligence, digital skills, and work readiness and how emotional intelligence and digital skills affect work readiness. The millennial generation can use this research to improve their work readiness by implementing emotional intelligence and digital skills.